ECUMENICAL MISSION IN INDONESIA: A Respon on Covid-19 Pandemic Situation - Simangunsong, Amran (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
Mission in ecumenical era is a new paradigm as the changing of time and the perspective of postmodern society. Recently, global people were challenged by pandemic situation that caused some shifts in the church ministry. This article offers some concept of mission which takes into account an interpretation to WCC declaration that is relevant to face pandemic situation in Indonesia. The writing method used is descriptive theological analysis with an ecumenical mission perspective. The result is that the mission of the church is to be present in the midst of the world to spread the word, help, love, and heal people affected by Covid-19 to become one.